Cell Based Therapy for Type 1 Diabetes: Should We Take Hyperglycemia Into Account? - Grohová, Anna; Dáňová, Klára; Špíšek, Radek; Palová-Jelínková, Lenka (Frontiers in Immunology, 2019)
Abstract Diabetes mellitus is characterized by long standing hyperglycemia leading to numerous life-threatening complications. For type 1 diabetes mellitus, resulting from selective destruction of insulin producing cells by exaggerated immune reaction, the only effective therapy remains exogenous insulin administration. Despite accurate compliance to treatment of certain patients, transient episodes of hyperglycemia cannot be completely eliminated by this symptomatic treatment. Novel immunotherapeutic approaches based on tolerogenic dendritic cells, T regulatory cells and mesenchymal stem cells (MSCs) have been tested in clinical trials, endeavoring to directly modulate the autoimmune destruction process in pancreas. However, hyperglycemia itself affects the immune system and the final efficacy of cell-based immunotherapies could be affected by the different glycemic control of enrolled patients. The present review explores the impact of hyperglycemia on immune cells while providing greater insight into the molecular mechanisms of high glucose action and subsequent metabolic reprogramming of different immune cells. Furthermore over-production of mitochondrial reactive oxygen species, formation of advanced glycation end products as a consequence of hyperglycemia and their downstream signalization in immune cells are also discussed. Since hyperglycemia in patients with type 1 diabetes mellitus might have an impact on immune-interventional treatment, the maintenance of a tight glucose control seems to be beneficial in patients considered for cell-based therapy.